User Access Link Impact on Web Browsing Quality - Kajackas, A.; Šaltis, A.; Vindašius, A. (Elektronika ir Elektrotechnika, 2010)
This paper analyzes the possibility to develop method of user perceived quality of service estimation and to create impartial monitoring system to track user perceived quality. We also propose passive method for user perceived quality estimation, which allows evaluating if actual quality of service achieved by network meets the quality declared by operator, and allows discovering if it is degraded. It is seen, that degradation of Web browsing quality is proportional to degradation of user access link available bit rate. In this paper presented development and testing of passive non-intrusive agent, implemented using tcpdump and libcap libraries, residing in user device for obtaining channel available bit rate, which can be used for evaluation of perceived quality of Web browsing service. Experimental data shows that throughput, perceived by user, depends not only on instantaneous available bit rate of the physical access link, but also on TCP transmission characteristics. Even though perceived quality of Web browsing is proportional to average bit rate of the channel, additional research is needed to define the exact input of channel bandwidth to perceived Web browsing quality. Ill. 8, bibl. 11 (in English; abstracts in English, Russian and Lithuanian).